Improving Client Satisfaction through Interdisciplinary teamwork - MOHAMAD BASSEM CHAMMA (مجلة العلوم الهندسية و تكنولوجيا المعلومات, 2018)
Recently the construction process has been criticized for being incapable, immature, corrupt and considerably more adversely. During a year ago pattern day of the group architectural division stakeholders. In this way some architecture firms in UAE ranges have freely started create and actualize their own particular undertakings, playing the part as designers and investment in the entire construction handle. However, it appears like the project directors at the design firms does not have the right abilities to handle the occurrence changes in the moving construction industry, even in the improvement of in-house projects, making it hard to remain ahead in the construction and architect advertise, with the point of making a more effective work process and a cost proficient construction process. Therefore, the research question is to be addressed: How Improving Construction Process Can Improve Client Satisfaction through Interdisciplinary teamwork.